Gentrifikasi Kawasan Permukiman Akibat Perkembangan Komersial dan Pariwisata di Kawasan Dago Giri, Bandung - Herniati Pratiwi; Reylin Azzahra; Dhia Khansa Kamilah; Fanesya Admirani Wilhemina; Agustian Rahayu (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The phenomenon of gentrification, which has impacted social, economic, and spatial changes in the Dago Giri area of Bandung, has been caused by rapid economic and tourism growth over the past twenty years. The purpose of this study is to identify the social, economic, and spatial impacts of the gentrification process and to examine how the growth of tourism activities is related to changes in settlement patterns. The research method used in descriptive qualitative by conducting literature research with secondary data sources such as books, journals, and new articles. The results show that the shift of the Dago Giri are from an agricultural environment and local settlement to a tourist and commercial area has caused an increase in land prices, the displacement of indigenous peoples, or dispersion, and changes in the social structure of the community. In addition, the shift in land use has caused social differences between newcomers and long-time residents, and less open green space. Although gentrification benefits investors and businesses, it is derimental to the local community. Therefore, inclusive spatial planning policies are needed to balance economic growth with social sustainability. These policies should include affordable housing, cost control, preservation of local character, and community land ownership.